PERANAN PERSONAL SELLING SEBAGAI SALAH SATU ALAT PROMOSI DALAM ASURANSI - Istiharini . (Bina Ekonomi, 2003)
People always face risks in life and they don't like it People want to share it with others, in this case the life insurance companies. People bought life insurance policies and pay the premium, and the insurance company gives protection in return.Buying insurance is buying protection. Unfortunately this idea doesn't work in Indonesia. Indonesian people still have the traditional perception about insurance that the premium of the insurance will be a burden for them. However since May 1998, because of the riots, people changed their view of insurance. They realize that they need protection. Therefore this opens a vast opportunity for much insurance company, to operate in Indonesia for both local and internationalCompetition emerged Insurance companies need marketing strategies in order to win the market. F'T.A.J.X cabang Bandung is one of the biggest insurance companies in Indonesia. They use highly trained insurance agents to market their products effectively. Personal selling is only one from many promotion mixes but it's a prominent promotion tool to sell unsought goods like insurance.